2021
DOI: 10.1111/geb.13382
|View full text |Cite
|
Sign up to set email alerts
|

Lianas and trees exhibit divergent intrinsic water‐use efficiency along elevational gradients in South American and African tropical forests

Abstract: Aim Elevational gradients provide excellent opportunities to explore long‐term morphological and physiological responses of plants to environmental change. We determined the difference in the elevational pattern of foliar carbon isotope composition (δ13C) between lianas and trees, and assessed whether this difference arises from changes in photosynthesis or stomatal conductance. We also explored the pattern of nutrient limitations with the elevation of these two growth forms. Location The study was conducted i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 74 publications
1
4
0
Order By: Relevance
“…We investigated trends in tree growth and leaf functional traits along an elevation gradient in the Australian Wet Tropics using a single, regionally important genus to gain insight into the responses of closely related species with differing elevational distributions. Observations in tropical rainforests on other continents have shown that tree growth rates and foliar δ 15 N typically decline with elevation (Bauters et al, 2017;Malhi et al, 2017), whereas LMA and foliar δ 13 C typically increase with elevation (Vitousek et al, 1990;Mumbanza et al, 2021). We confirmed from our field-based observations that similar trends also occur in Flindersia species in Australian tropical rainforests.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…We investigated trends in tree growth and leaf functional traits along an elevation gradient in the Australian Wet Tropics using a single, regionally important genus to gain insight into the responses of closely related species with differing elevational distributions. Observations in tropical rainforests on other continents have shown that tree growth rates and foliar δ 15 N typically decline with elevation (Bauters et al, 2017;Malhi et al, 2017), whereas LMA and foliar δ 13 C typically increase with elevation (Vitousek et al, 1990;Mumbanza et al, 2021). We confirmed from our field-based observations that similar trends also occur in Flindersia species in Australian tropical rainforests.…”
Section: Discussionsupporting
confidence: 85%
“…Foliar δ 13 C and δ 15 N have been used as indicators of intrinsic water-use efficiency (Cernusak et al, 2013), and ecosystem nitrogen cycling (Martinelli et al, 1999), respectively. However, although some of these trends with increasing elevation appear to be general in the literature (Vitousek et al, 1990;Bauters et al, 2017;Mumbanza et al, 2021), the mechanisms driving the observations are not fully resolved. Disentangling the direct and indirect role that temperature plays in determining these trends in plant functional traits is vital to understanding elevation gradients as proxies for predicting the response of forests to future climate scenarios.…”
Section: Introductionmentioning
confidence: 90%
“…The higher leaf water potentials in lianas suggest stronger stomatal control compared to trees, which allows lianas to reduce the variation in leaf water potentials by limiting transpiration (E) through reduced stomatal conductance (G s ) (Tyree & Sperry, 1988; Cochard et al ., 2002; Sperry et al ., 2002). Since such stronger stomatal control may lead to a higher water use efficiency (the ratio of biomass accumulation to water lost) (Sinclair et al ., 1984; Tardieu, 2013; Lawson & Blatt, 2014), this may allow the lianas under study here to maintain leaf productivity while preventing excessive dehydration under drier environmental conditions (Sinclair et al ., 1984; Mumbanza et al ., 2021). Such mechanisms may thus appear in the liana and tree communities under study here, as well as in liana communities in other forests (Andrade et al ., 2005; Chen et al ., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…high water transport capacity) resulting from their wide and long xylem elements (Ewers et al ., 1991) may allow lianas to reduce water potential differences between soil and leaves, enabling high tissue water potentials and positive turgor potentials during drought. High water use efficiency resulting from strong stomatal control (Cai et al ., 2009; Chen et al ., 2015) may allow lianas to maximize gas exchange and growth while preventing excessive dehydration (see also Mumbanza et al ., 2021). Additionally, a high accumulation of nonstructural carbohydrates for osmoregulation and hydraulic function (O’Brien et al ., 2014; Martínez‐Vilalta et al ., 2016) and reductions in leaf area (Lambers & Oliveira, 2019) could also explain the maintenance of high water status and turgor potentials in lianas during seasonal drought.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al (2020) [ 24 ] found that wind speed affected the boundary layer of the air on the leaf surface, which decreased the resistance for gas exchange and the exchange of CO 2 and H 2 O between the leaf interior and ambient atmosphere, thereby influencing the leaf WUE. In addition, since climatic factors change with geographical factors, intrinsic WUE changes with geographical factors [ 25 , 26 ]. Although many previous works have focused on the relationships between plant WUE and climatic factors [ 15 ], most of these studies were concentrated mainly on arid and semiarid climate regions, or the research objects were mostly one or several plants [ 19 , 22 , 27 ]; in contrast, few studies have focused on tropical regions with high temperature and rainfall.…”
Section: Introductionmentioning
confidence: 99%